The Influence of Health Literacy with Consumption and Exercise Behavior among School-age Children with Overnutrition - Anonjarn, Kanlayawee; Odomporn, Orapun (Journal of The Royal Thai Army Nurses, 2021)
The problem of overnutrition in children is still a significant problem. Therefore, the study of health literacy to prevent obesity is essential. The purpose of this research was to study health literacy consumption and exercise behavior ,Predictive factors of personal, family, and environmental factors With consumption and exercise behavior and factors predicting health literacy and consumption and exercise behaviors . Our sample included 100 students who are over nutritional status with age of 9-14 years old in Nakhon Ratchasima province. Data were collected by using questionnaires. Data were analyzed by using descriptive statistics. And the analysis of multiple regression. The result of the research shows that predicting factors of the individual, family, and environmental among school-age children with overnutrition include gender (male) (β = -.268), marital status of parents (living together) (β = - .340) able significant predicted of the consumption and exercise behaviors to 18.7% (R2 = .187, F = 7.353) predicting factors of health literacy among school-age children with overnutrition include self-management. (β = .588) Decision skill. (β = .213) Cognitive. (β = .207) able significant predicted of the consumption and exercise behaviors to 22.5% (R2 = .225, F = 4.503)